Efficacy of Repositioning Therapy in Patients With Benign Paroxysmal Positional Vertigo and Preexisting Central Neurologic Disorders - Chen, Chih-Chung; Cho, Hsiao-Shan; Lee, Hsun-Hua; Hu, Chaur-Jong (Frontiers in Neurology, 2018)
With the exception of migraines, benign paroxysmal positional vertigo (BPPV) in patients with preexisting central neurologic disorders (CND) is rarely discussed in the literature. Demographic features of this patient group and the efficacy of repositioning therapy are still unknown. We hypothesized that a CND may alter the function of the central vestibular pathway, thus changing the pattern of BPPV and outcomes of repositioning. In this study, we enrolled 93 consecutive idiopathic BPPV patients and categorized them into two groups according to the presence or absence of a CND. In our series, 31.2% of BPPV cases had a CND. The most common associated CNDs were cerebrovascular disease and migraines. The two groups showed similar age distributions, canal involvement, success rates of repositioning, and cycles of treatment used to achieve complete resolution. The major differences were the proportion of females (89.7%) and a right-side predominance (75.9%) in the CND group. There was a trend of more residual dizziness (RD) after successful repositioning in the CND group, but the difference was not significant. The reason for the female and right-side predominance in the CND group is unclear. We concluded that the efficacy of repositioning therapy was excellent (with a success rate of 80.6% with one cycle and 93.5% within two cycles of treatment) for BPPV with or without a preexisting CND. Clinicians are encouraged to diagnose and treat BPPV in patients with a preexisting CND as early as possible to improve patients' quality of life, avoid complications, and reduce medical costs.